In Situ and Ex Situ Studies of Molybdenum Thin Films Deposited by rf and dc Magnetron Sputtering as a Back Contact for CIGS Solar Cells - K. Aryal; H. Khatri; R. W. Collins; S. Marsillac (International Journal of Photoenergy)
Molybdenum thin films were deposited by rf and dc magnetron sputtering and their properties analyzed with regards to their potential application as a back contact for CIGS solar cells. It is shown that both types of films tend to transition from tensile to compressive strain when the deposition pressure increases, while the conductivity and the grain size decreas. The nucleation of the films characterized by in situ and real time spectroscopic ellipsometry shows that both films follow a Volmer-Weber growth, with a higher surface roughness and lower deposition rate for the rf deposited films. The electronic relaxation time was then extracted as a function of bulk layer thickness for rf and dc films by fitting each dielectric function to a Drude free-electron model combined with a broad Lorentz oscillator. The values were fitted to a conical growth mode and demonstrated that the rf-deposited films have already smaller grains than the dc films when the bulk layer thickness is 30 nm.